Food education for nutritional health. School, environment, media and mediations (2020)
ABSTRACT: The school age, being the one with the highest brain uptake for learning, is the privileged one for formal education and life education, such as the formation of habits, attitudes, and knowledge, which, over time, once incorporated, constitute a lifestyle, that largely determines the quality of life, which involves the conditions and health status of individuals at later stages. Along with home or family, school is considered the most important environment for the formation of a schoolchild, and in it, not only the thematic knowledge transmitted from the academic programs by areas of knowledge similar to geography, social or mathematics is important, but how they are treated in and out of the classroom, that is, the means with which they are intentionally addressed in class, and how they are presented by each teacher, such as those that in a natural way flow as messages from the social environment, through interaction with other people, with advertising, with social dynamics, with spaces or events, that facilitate the student relating to previous experiences and knowledge to reach conclusions and make decisions for their own life and immediate environment. The educator for nutritional health must be fully aware of the scope of his actions and must guide them wisely. The difference between information, communication and education is based on the scope, intentionality, objectives, and strategies used; therefore, to discern about the school environment and its influences, to use the available or required means in a relevant and appropriate manner, as well as the role of significant adults as mediators and other individuals, is their challenge.